Megalopolis unbound: Knowledge collaboration and functional polycentricity within and beyond the Yangtze River Delta Region in China, 2014. (February 2018) - Li, Yingcheng; Phelps, Nicholas
Recent work on world city networks, urban polycentricity and megapolitan urban forms share an interest in the economic functionality of inter-city linkages. The intersection of these bodies of literature is in the often overlooked defining features of megalopolitan forms – their being the 'hub' that links national to international urban systems and the 'incubator' within national urban systems (Gottmann, 1976). With this intersection in mind, this paper measures the functional polycentricity of China's Yangtze River Delta Region (YRDR) at different geographical scales from an intercity knowledge collaboration perspective. The paper uses data on co-publications as an indicator of knowledge linkages between cities within and beyond this megalopolis. The YRDR can be seen as functionally polycentric at the megapolitan scale but this functional polycentricity decreases with increases in the geographical scale at which interurban linkages are considered. Furthermore, a multi-scalar analysis of functional polycentricity helps identify the hub role of Shanghai. The results show that Shanghai's knowledge hub role is currently present at the national scale. It may take some time for Shanghai to become a knowledge hub at the global scale given its not-so-strong international links and relatively weak local links. The paper concludes with some suggestions for future research agendas.